Community-Based Analysis of Anemia Risk Factors in Pregnant Women at Primary Healthcare - Anita Dahliana; Adinda Rizkita N. H; Chentya Catheriane L; Geraldy Aziz S. H; Isro Rafidatus S; Ketut Ayu O. S; Rinandha Yusfahreza W; Dyan Eka Puspitasari; Farida Yan Pratiwi Kurnia (Postgraduate, University of Mataram, 2025)
Anemia during pregnancy remains a significant public health concern, particularly in developing countries, where it contributes to adverse maternal and fetal outcomes. Data from Puskesmas Kebomas, Gresik, indicates that between July 2022 and June 2023, there were 167 cases of anemia among pregnant women across 11 villages. Anemia in pregnant women is influenced by various factors, including gestational age, parity, dietary patterns, infections during pregnancy, education level, economic status, and adherence to iron tablet consumption. In Kebomas District, Kedanyang Village recorded the highest number of anemia cases among pregnant women. This study was a descriptive cross sectional study using questionnaire for determine the risk of anemia in pregnant woman in Desa Kedanyang, Kebomas through interview. The result will processed to find the cause of anemia. Incidence of anemia in pregnancy in Desa Kedanyang, Kebomas is disobedient of consuming iron tablets (21 people) and the pregnancy interval less than 2 years (16 people). Conclusion: The incidence of anemia in pregnancy Desa Kedanyang, Kebomas is mostly caused by non-compliance with the consumption of iron tablets and a pregnancy interval less than 2 years.